Security of Germany and the US Military Presence: A “Comfortable” Occupation or an Allied Solidarity? - Artem Sokolov (Международная аналитика)
The article is devoted to the influence of the American military presence in Germany on the foreign policy strategy of the German leadership in the matter of ensuring the security of Germany. The location of the US Army in a number of German lands has remained a significant factor in German foreign policy since the founding of the Federal Republic of Germany in 1949. After the reunification of Germany in 1990, the German government expanded its foreign policy activity based on the system of Western alliances and a multilateral approach. The crisis in the Western community, exacerbated by the actions of the administration of the Donald Trump, raised among the German elites concerns regarding the reliability and predictability of the overseas ally. Despite the declarative statements of German officials about the intention to strengthen the defense potential of the EU, German politicians face difficulties in finding alternatives to US security guarantees.